Continuing breastfeeding upon returning to work: feelings, challenges and strategies of breastfeeding nurses - Lourdes Maria Nunes Almeida; Maithê de Carvalho e Lemos Goulart; Fernanda Garcia Bezerra Góes; Fernanda Maria Vieira Pereira-Ávila; Carina Bulcão Pinto; Aline Cerqueira Santos Santana da Silva; Luana Ramos Garcia; Larissa Sousa Oliva Brun (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To describe feelings, challenges and strategies related to the continuity of breastfeeding after returning to work in the perception of lactating nurses. Method: Descriptive, exploratory, qualitative study, with snowball sampling. Data collection occurred virtually between August and September 2020 in the State of Rio de Janeiro. Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires software and a thematic analysis were used. Results: 42 breastfeeding nurses participated and cited fear, missing the child, anguish, and pleasure in returning to work. Challenges such as lack of infrastructure for pumping the breast in health services, unfavorable scales, and multiple jobs were reported. Support networks, listening spaces, and appropriate times and places for breast milk pumping were mentioned as strategies. Conclusion: Different feelings and challenges for the continuity of breastfeeding upon returning to work were identified; some strategies found were common to other working women while others related to the specific nursing work context.